Effect and mechanism of modified Yougui power on Simmental bulls with oligoasthenozoospermia based on targeted amino acid metabolism - Chen, Baoxia; Ma, Qiang; Ma, Huifang; Zhang, Wenfei; Wu, Runmin; Niu, Chun; Guo, Rongxia; Ma, Zhiyuan; Ji, Peng; Wei, Yanming; Hua, Yongli (Frontiers in Veterinary Science, 2025)
ObjectiveOligoasthenozoospermia (OA) is a common reproductive disorder characterized by reduced sperm count and motility in animals. Yougui Pill (YP) is a traditional Chinese medicine formula for the treatment of oligoasthenozoospermia. However, its effects on Simmental bulls are relatively limited, and the mechanisms involved in the regulation of OA remain unknown.MethodsIn this study, antler gum was removed from the original formula, and the key components and their mechanism of action of Modified Yougui Power (MYP) for the treatment of OA were investigated by UPLC-MS/MS analysis, amino acid metabolomics studies, and molecular docking analysis. UPLC-MS/MS was used to detect and study the active compounds of MYP. The levels of T, E2, FSH, and LH in the serum of OA and the control group were detected by enzyme-linked immunosorbent assay (ELISA). The levels of amino acid metabolites and related metabolic pathways in semen of the OA and control groups were detected by UHPLC-MRM-MS/MS. Molecular docking was used to assess the affinity between the primary active ingredients associated with OA and their core targets.ResultsThe main components of MYP include trehalose, morroniside, hypaconitine, loganin, quercetin, kaempferol, and other compounds. MYP treatment improved sperm count, sperm motility, and expression of T, E2, and FSH in OA bulls. Amino acid metabolomics analysis revealed that MYP treatment influenced 67 metabolites in comparison to the OA group. Among these, 47 amino acid metabolites were found to be upregulated, including Arginine, Phenylalanine, and Serine, among others. Conversely, 20 amino acid metabolites exhibited downregulation. The discovery of cysteine and methionine metabolism, glycine, serine, and threonine metabolism, alanine, aspartate, and glutamate metabolism, arginine biosynthesis, D-amino acid metabolism, the biosynthesis of phenylalanine, tyrosine, and tryptophan, as well as the mTOR signaling pathway, are significant metabolic pathways. Molecular docking results validated robust binding interactions between these active ingredients and their respective core targets.ConclusionMYP exhibits significant therapeutic potential for OA in Simmental bulls by regulating hormone expression and restoring amino acid metabolic homeostasis. This present study elucidates the complex mechanisms through which MYP exerts its effects in the treatment of OA, thereby providing new evidence for understanding the pharmacological properties of traditional Chinese medicine for OA from multiple perspectives. Furthermore, MYP may represent a cost-effective therapeutic option for the treatment of OA in animals.